SIFAT KIMIA DAN FISIK TANAH YANG BERPENGARUH TERHADAP PRODUKSI BAWANG DAUN (Allium fistulosum L) SERTA NILAI EKONOMI LAHAN PADA BERBAGAI KETINGGIAN (Studi Kasus di Wilayah Pacet, Cianjur, Jawa barat) - Wulanningtyas, Heppy Suci; Malik, Afrizal (Universitas Sebelas Maret, 2015)
This research aims to (1) identification the effect of soil physical and chemical characteristics to the yield of green onion planted from 800 - 1.400 metres above sea level (mdpl), (2) identification of fertilizer and elevation effect, (3) identification of landrent with potential development. The experimental plots were located in Pacet, Cianjur Regency, West Java. This research utilize primary data of soil physical and chemical characteristics that is pH, C-Organic, Total N, P, Ca, Mg, K, Na, KTK, KB, Al, H, Fe, Cu, Zn, Mn, sand, dust and clay texture.By employing Forward Stepwise – Multiple Regression, it was showed that Fe has a positive effect to green onion production at the non fertilized farmland, while Na and Al have negative effects. Adversely, at the fertilized farmland, all significant factors have negative effect, a case in point : elevation, Zn element and sand texture. Fertilization has a positive effect to green onion production at all level of elevation. Non fertilized farmland could produce average yield of onion production from 800 - 1.400 mdpl successively as follows : 13.395,1 kg/ha, 17.263,4 kg/ha, 14.351,9 kg/ha and 15.802,5 kg/ha. While fertilized farmland could produce average yield of onion production from 800 - 1.400 mdpl successively as follows : 18.172,8 kg/ha, 23.415,6kg/ha, 20.655,3 kg/ha and 20.853,9 kg/ha. Fertilization can increase productivity, and the highest productivity was reached at 1.000 mdpl. The highest landrent reached at 1.400 mdpl. The landrent from 800 - 1.400 mdpl are Rp. 9.151 /m2, Rp. 8.386/m2,Rp.7.337/m2 and Rp. 10.522/m2.